New finds of species of the genus Asplenium L. in Kherson region (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
Asplenium ceterach L. and Asplenium trichomanes L. were firstly found for Kherson region. First species was collected in Chervonyi Mayak village, Berislav district, Kherson region, and second was found in Kherson city. Both species grow on the building walls. The ecological characters, habitats and population state were studied.
Keywords: Asplenium ceterach, Asplenium trichomanes, Kherson region.